Studi Komparasi Perancangan Balok Struktural Berdasarkan SNI 2847-2002, SNI 2847-2013 Dan SNI 2847-2019 - Noerman Adi Prasetya; Ahmad Hernadi; Agung Nugroho (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
This study aims to determine the difference in structural beam design using SNI 2847-2002, SNI 2847-2013 and SNI 2847-2019 by comparing the bending and shear reinforcement in the case study of the Faculty of Health Sciences Building, University of Borneo Tarakan. The results of the comparisons include: the maximum reinforcement ratio at SNI 2847-2013 and 2019 is around 16,667% smaller than SNI 2847-2002, the flexural capacity of the beam design results from SNI 2847-2013 and 2019 increases by about 12.5% compared to SNI 2847-2002, The shear capacity of concrete (Vc) designed with SNI 2847-2013 and 2019 increased by about 2% compared to SNI 2847-2002, as well as the design shear capacity of the accumulated concrete and shear reinforcement designed by SNI 2847-2013 and 2019 increased no more than 1% compared to SNI 2847-2002.